Simultaneous Hopf and Bogdanov–Takens Bifurcations on a Leslie–Gower Type Model with Generalist Predator and Group Defence - (:unkn) unknown (Springer Nature Switzerland, 2024)
In this work, we analyze a two-dimensional continuous-time differential equations system derived from a Leslie–Gower predator–prey model with a generalist predator and prey group defence. For our model, we fully characterize the existence and quantit...
Keywords: Bifurcaciones dinámicas; Modelos depredador-presa